The gender gap in brazilian entomology: an analysis of the academic scenario. - HIPÓLITO, J. (2021)
Although women are about half of world's population, they are underrepresented in many sectors including academia and the research scenario in general. Gender gap in Entomology has been pointed out in other publications; however, data for Brazil has never been demonstrated. Here we provide a diagnosis for the Brazilian Entomology scenario in order to contribute to propositions towards disentangling the gender gap in general. We analyzed scientometric data for Brazilian Entomology focusing on gender disparity and on personal perceptions related to the gender gap through an online questionnaire. We detected a pervasive gender bias in which the scissor-shaped curve is the most representative effect of it: women were the majority in lower degree stages but the minority in higher degree stages (permanent positions and positions of prestige and power). We also observed mentorship bias and discussed these results in light of intersectionality and the COVID-19 pandemic. Gender differences were perceived differently by the questionnaire respondents considering age, gender, and parenting. With this data and analyses, we have provided elements to stimulate and support change to a healthier and more equitable academic space.